Surface mass balance over the past three decades (1986-2017) derived from radar stratigraphy dated with ice cores over the Djupranen Ice Rise, Leningradkollen Ice Rise, and the Nivlisen Ice Shelf, central Dronning Maud Land, Antarctica - Pratap, Bhanu; Matsuoka, Kenichi; Meloth, Thamban (Norwegian Polar Institute, 2021)
Surface mass balance (SMB) for varying time periods in the past three decades were obtained by dating tracked radar reflectors. These estimated cover two ice rises (Djupranen and Leningradkollen) and the Nivlisen Ice Shelf between them in central Dronning Maud Land. This dataset consists of (i) processed radargrams used to obtain the SMB (ii) tracked reflectors with age, two-way travel time, depth, and estimated SMB and, (iii) period wise surface mass balance estimates. The data are presented as: (i) Daily retrieved (year/month/date) processed radargrams as HDF structure files consisting of following variables: • lon: longitudes in decimal degrees • lat: latitudes in decimal degrees • x: x coordinate (m) in a polar stereographic projection EPSG:3031 • y: y coordinate (m) in a polar stereographic projection EPSG:3031 • z: elevations (m) above the WGS84 ellipsoid • wfm: matrix with radar amplitude data. • fwfm: filtered wave form i.e. matrix with radar amplitude data. • dist: distance (m) from the starting point along the profile • twt: two-way-travel time (ns) vector (ii) Each ‘reflectors_age_depth_SMB’ files consisting of tracked reflectors and associated SMB (meter ice equivalent per year or m i.e. a-1). Each file has following variables: • name: name of the reflector tracked • lon: longitudes in decimal degrees • lat: latitudes in decimal degrees • x: x coordinate (m) in a polar stereographic projection • y: y coordinate (m) in a polar stereographic projection • twt: two-way-travel time (ns) • age (years): age of reflector (with reference to year 2016/2017 surface) • SMB: surface mass balance (m i.e a-1) • depth: Ice equivalent depth (m i.e.) from the surface 2016/2017 (iii) ESRI shapefiles consisting of SMB in meter ice equivalent (m i.e. a-1) for a specific period. Each file has following variables: • name: name of the reflector tracked with the years and period • x: x coordinate (m) in a polar stereographic projection • y: y coordinate (m) in a polar stereographic projection • SMB: surface mass balance (m i.e a-1)